Design of the transmitter coil used in wireless power transfer system based on genetic algorithm - Konghirun, Mongkol; Nutwong, Supapong; Sangswang, Anawach; Hatchavanich, Nattapong (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Performance of the wireless power transfer (WPT) system relies on the physical dimensions of the coupled coil, which should be optimally designed to meet required system performance and reduce the operating cost. This paper presents an optimal design based on genetic algorithm (GA) for the transmitter coil used in wireless power transfer system. Physical parameters of the circular flat spiral coil, including wire’s cross-sectional area, coil’s inner diameter, coil’s outer diameter, coil’s turn number, and space between each turn of the coil are considered. The design objective is to minimize the total wire length required by the coil subjected to both linear and nonlinear constraints. The design process is implemented on MATLAB optimization toolbox which is simple and accurate. The validity of proposed optimal coil design is verified by the experiment, which indicates that total wire length of the optimized coil can be reduced by 5.5 percent compared to the conventional coil without sacrificing the system performance. System efficiency obtained from the optimized coil can be improved up to 8.32 percent.